Práticas pedagógicas: contribuições para pensar em uma educação emancipadora - Moreira, Amanda Miranda [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
This research is part of the work that I developed as a student researcher participating in the project Pedagogical practice of group work at school: rescue of narrative and teachers´ knowledge. The project was developed in a Rio Claro City Public school (2010-2011).I weekly attended that school for two years, following the pedagogical work of a teacher. During this period, her practices caught my attention, especially the way that she looked at the social context and the life stories of her students. For this reason, I propose to develop a qualitative research with the objective of examining the pedagogical practice of a elementary school teacher (initial series) and understand the extent to which her practices favor the emancipation of students. I intend to extend/apply the concept of emancipation from the theoretical perspective of Paulo Freire. The data will be obtained from the following documents: my records (notebook 1-2010 and notebook 2-2011); letters elaborated by me and sent to the teacher; letters written by the teacher and sent to me; articles produced by this teacher and her work plans. The research intends to contribute to the legitimacy of teacher knowledge in daily school

Esta pesquisa é parte do trabalho que desenvolvi como aluna pesquisadora ao participar do projeto de pesquisa “Prática pedagógica do trabalho coletivo na escola: resgate da narrativa e dos saberes dos professores”. O projeto foi desenvolvido em uma escola da rede municipal de Rio Claro (2010-2011). Estive inserida na escola no período de dois anos acompanhando semanalmente o trabalho pedagógico de uma professora. Ao longo desse período, seu olhar atento ao contexto social e às histórias de vida de seus alunos chamou minha atenção. Por este motivo, proponho desenvolver uma pesquisa qualitativa com o objetivo de analisar, a prática pedagógica de uma professora do Ensino Fundamental I e compreender em que medida suas práticas favorecem a emancipação dos alunos. Pretendo aprofundar o conceito de emancipação a partir da perspectiva teórica de Paulo Freire. Os dados serão obtidos a partir dos seguintes documentos: meus registros (caderno1- 2010 e caderno2-2011), cartas elaboradas por mim e encaminhadas à professora, cartas escritas pela professora e dirigidas a mim, artigos produzidos pela professora e seus planos de trabalho. A pesquisa pretende contribuir com a legitimação dos saberes docentes produzidos no cotidiano escolar
Keywords: Professores - Formação; Pratica de ensino; Ensino fundamental; Crianças - Desenvolvimento